Solar‐induced dorsal skin necrosis in sheep. Issue 5 (24th July 2019) - García, Juan A.; Romero, Agustín; Uzal, Francisco A.; Tarigo, Laura; Affolter, Verena K.; Dutra, Fernando
Abstract : Background: Solar‐induced thermal burns of dark skin over the dorsum have been reported in dogs, sheep and a pig. Objectives: This report describes an outbreak of solar‐induced thermal burns over the dorsal skin of criollo and Texel sheep in Uruguay. Animals and methods: Cross‐bred criollo and pure‐bred Texel adult ewes from a flock of 80 animals presented with severe skin lesions. Eight animals were evaluated clinically and skin biopsy specimens were collected from three ewes for histopathology. Epidemiological data were collected. Results: Black/brown criollo sheep presented with extensive, wide, linear dorsal skin necrosis extending from the interscapular to the lumbosacral area. Necrotic skin was firm, dry and largely detached from the underlying subcutis. Nonpigmented Texel sheep showed milder lesions with rapid re‐epithelialization and healing. Histological features were consistent with third‐degree burns, characterized by full‐thickness coagulative necrosis of epidermis and dermis, including blood vessels and adnexa. The cumulative incidence of the disease was 21% during the 30 days post‐shearing, affecting 50% of criollo and 7.4% of Texel sheep ( P  < 0.001). Conclusions: The findings are consistent with post‐shearing, sun‐induced thermal burns leading to dorsal skin necrosis. Risk factors include sunlight exposure during hot months after shearing, dark skin and obesity. Abstract : Background – Solar‐induced thermal burns of dark skin over the dorsum have been reported in dogs, sheep and a pig.Objectives – This report describes an outbreak of solar‐induced thermal burns over the dorsal skin of criollo and Texel sheep in Uruguay.Conclusions – The findings are consistent with post‐shearing, sun‐induced thermal burns leading to dorsal skin necrosis. Risk factors include sunlight exposure during hot months after shearing, dark skin and obesity. Résumé: Contexte: Les brulures thermiques liées au soleil de la peau noire du dos ont été décrites chez le chien, le mouton et un porc. Objectifs: Cet article décrit une apparition de brulures thermiques liées au soleil sur la peau dorsale de moutons Criollo et Texel en Uruguay. Sujets et méthodes: Des brebis adultes criollo croisées et Texel pure race issues d'un cheptel de 80 têtes ont été présentées avec des lésions cutanées sévères. Huit animaux ont été examinés cliniquement et des biopsies cutanées ont été prélevées pour trois brebis pour histopathologie. Des données épidémiologiques ont été collectées. Résultats: Les criollo noir/marron ont été présentés avec des lésions cutanées dorsales nécrosantes, linéaires, dorsales extensives de la zone interscapulaire à lombo‐sacrée. La peau nécrotique était ferme, sèche et largement détachée du tissu sous cutanée sous jacent. Les Texel non pigmentés montraient des lésions plus modérées avec une ré‐épithélialisation et cicatrisation rapides. Les données histopathologiques étaient compatibles avec des brulures de troisième degré, caractérisées par une nécrose de coagulation de toute l'épaisseur de l'épiderme et du derme, y compris les vaisseaux sanguins et les annexes. L'incidence cumulative de la dermatose était de 21% au cours des 30 jours suivant la tonte, affectant 50% des criollo et 7, 4% des Texel (P < 0.001). Conclusions: Les données étaient compatibles avec des brulures thermiques liées au soleil après la tonte menant à une nécrose dorsale. Les facteurs de risque incluent l'exposition au soleil au cours des mois chauds après la tonte, la peau noire et l'obésité. Resumen: Introducción: se han descrito quemaduras térmicas solares en piel oscura del dorso en perros, ovejas y cerdos. Objetivos: este artículo describe un brote de quemaduras térmicas inducidas por el sol en la piel dorsal de ovejas criollas y Texel en Uruguay. Animales y métodos: ovejas criollas mestizas y hembras adultas de raza Texel de una manada de 80 animales se presentaron con lesiones cutáneas graves. Ocho animales fueron evaluados clínicamente y se tomaron muestras de biopsia de piel de tres ovejas para histopatología. Se recogieron datos epidemiológicos. Resultados: Las ovejas criollas negras/marrones se presentaron con una extensa necrosis dorsal lineal de la piel desde el área interescapular a la lumbosacra. La piel necrótica era firme, seca y en gran parte separada del subcutis subyacente. Ovejas Texel no pigmentadas mostraron lesiones más leves con reepitelización y curación rápidas. Las características histológicas fueron consistentes con quemaduras de tercer grado, caracterizadas por necrosis coagulativa de epidermis y dermis de espesor completo, incluidos vasos sanguíneos y anexos. La incidencia acumulada de la enfermedad fue del 21% durante los 30 días posteriores a la esquila, afectando al 50% de las ovejas criollas y al 7, 4% de Texel ( P <0, 001). Conclusiones: los hallazgos son consistentes con quemaduras térmicas inducidas por el sol tras el esquilado causando necrosis dorsal de la piel. Los factores de riesgo incluyen la exposición a la luz solar durante los meses calurosos después del esquilado, piel oscura y obesidad. Zusammenfassung: Hintergrund: Es wurden Sonnen‐induzierte thermale Brandwunden auf dunkler Haut über dem Dorsum bei Hunden, Schafen und bei einem Schwein beschrieben. Ziele: Dieser Bericht beschreibt den Ausbruch einer Sonnen‐induzierten thermalen Brandwunde über der dorsalen Haut von Criollo und Texel Schafen in Uruguay. Tiere und Methoden: Criollo‐Kreuzungen und reinrassige erwachsene Texelschafe aus einer Herde mit 80 Tieren, wurden mit schweren Hautveränderungen vorgestellt. Acht Tiere wurden klinisch evaluiert und von drei Mutterschafen wurden Hautbiopsieproben für eine histopathologische Untersuchung entnommen. Es wurden epidemiologische Daten gesammelt. Ergebnisse: Schwarz/braune Criollo Schafe wurden mit einer extensiven, weitläufigen, linearen dorsalen Hautnekrose vorgestellt, die sich von der Interskapular‐ bis zur Lumbosakralgegend ausdehnte. Die nekrotische Haut war derb, trocken und weitgehend von der darunterliegenden Subkutis abgelöst. Die nichtpigmentierten Texelschafe zeigten mildere Veränderungen mit einer schnellen Re‐Epithelialisierung und Heilung. Die histologischen Merkmale waren vereinbar mit Brandwunden dritten Grades, charakterisiert durch eine koagulierende Nekrose durch die gesamte Dicke der Epidermis und der Dermis, inklusive der Blutgefäße und Adnexa. Das kumulative Auftreten der Erkrankung war zu 21% während der ersten 30 Tage nach der Schur, was 50% der Criollo und 7, 4% der Texelschafe ( P < 0, 001) betraf. Schlussfolgerungen: Die Befunde sind im Einklang mit thermalen durch die Sonne induzierte Wunden nach der Schur, welche zu einer dorsalen Hautnekrose führen. Risikofaktoren waren die Sonnenlichtexposition während der heißen Monate nach der Schur, eine dunkle Haut und Adipositas. 要約: 背景: 犬、羊、および豚では、背部に見られる黒色の皮膚における太陽熱関連熱傷が報告されている。 目的: 本研究の目的は、ウルグアイのcriolloおよびTexel羊の背部の皮膚上の太陽熱による熱傷の発生について説明することである。 被験動物と方法: 交配criolloおよび純血Texel羊の成雌羊は、80頭の動物群が重度の皮膚病変を呈した。8頭の動物を臨床的に評価し、組織病理学のために皮膚生検標本を3頭の雌から採取した。疫学データを収集した。 結果: 黒/褐色criollo羊は、肩甲骨間から腰仙部まで広がる、幅広に線状の背側皮膚壊死を示した。壊死した皮膚領域は、硬く、乾燥しており、そして下にある皮下組織から大部分は剥がれていた。無色素のTexel羊は急速な再上皮化と治癒を伴うより軽度の病変を示した。組織学的特徴は、血管および付属器を含む表皮および真皮の全層性凝固壊死を特徴とする3度熱傷と一致した。疾患の累積発生率は、刈り込み後30日間で21%であり、criollo羊の50%およびTexel羊の7.4%が罹患していた(P <0.001)。 結論: 本知見は、背部皮膚の壊死を招く刈り込み後の太陽熱による熱傷と一致している。リスク因子には、刈り込み後の暑い時期の日光曝露、黒色皮膚、肥満が含まれる。 摘要: 背景: 据报道, 犬、羊和猪背部深色皮肤可发生日晒热灼伤。 目标 : 本报告描述了乌拉圭克里奥罗和特塞尔羊背部皮肤的日晒热灼伤。 动物和方法: 80只杂种的克里奥罗和纯种的特塞尔成年母羊, 表现出严重的皮肤病变。对八只动物进行临床评估, 从三只母羊身上收集皮肤活检样本用于组织病理学, 并收集流行病学数据。 结果: 黑色/棕色克里奥罗绵羊从肩胛间延伸到腰骶部, 呈现广泛、宽、线性背部皮肤坏死。坏死的皮肤坚硬、干燥并且大部分与皮下组织分离。浅色特克塞尔羊表现出较轻的病变, 上皮再生和愈合较快。组织学特征与三度烧伤一致, 其特征在于表皮和真皮的全层(包括血管和毛囊附件)凝固性坏死。在剪毛后30天内, 该疾病的累积发病率为21%, 其中分别为50%的克里奥罗和7.4%的特塞尔绵羊发病(P <0.001)。 结论: 这些发现与剪毛后的日晒热灼伤(导致背部皮肤坏死)一致。风险因素包括剪毛后炎热月份的阳光照射、深色皮肤和肥胖。 Resumo: Contexto: Queimaduras na pele escura do dorso induzidas por exposição solar já foram relatadas em cães, ovelhas e porcos. Objetivos: Este relato descreve um surto de queimaduras térmicas induzidas por radiação solar na pele do dorso de ovelhas criollo e Texel no Uruguai. Animais e métodos: Ovelhas adultas mestiças de criollo e puro sangue Texel de um rebanho de 80 animais apresentaram lesões cutâneas graves. Oito animais foram avaliados clinicamente e espécimens de biópsia cutânea foram coletados de três ovelhas para histopatologia. Dados epidemiológicos foram coletados. Resultados: As ovelhas criollo marrons apresentaram necrose cutânea extensiva, ampla e linear na pele do dorso, da área interescapular até a área lombossacral. A pele necrótica era firme, seca e amplamente desprendida do subcutâneo adjacente. As ovelhas Texel despigmentadas apresentaram lesões mais leves com rápida re‐epitelização e cicatrização. As características histológicas foram consistentes com queimadura de terceiro grau, caracterizadas por necrose coagulativa completa da epiderme e derme, incluindo vasos sanguíneos e anexa. A incidência cumulativa da doença foi de 21% durante 30 dias pós tosquia, afetando 50% das ovelhas criollo e 7, 4% das ovelhas Texel ( P < 0.001). Conclusões: Os achados foram consistentes com queimadura induzida por radiação solar pós tosquia, levando a necrose cutânea dorsal. Os fatores de risco incluem exposição solar durante os meses quentes após tosquia, pele escura e obesidade.